1995
DOI: 10.1520/jfs13760j
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Stature from the Length of the Cervical, Thoracic, and Lumbar Segments of the Spine in American Whites and Blacks

Abstract: In order to estimate stature from the length of cervical, thoracic, lumbar, thoraco-lumbar (T-L) and cervico-thoracolumbar (C-T-L) segments of the spine, measurements were made on white and black Americans, both male and female, autopsied during 1977–1993. Sample sizes were as follows: white males = 167; white females = 58; black males = 43; black females = 31. Separate measurements were made of the vertebral segments along the anterior surface of the spine. Regression formulae were calculated for each segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 4 publications
3
53
2
Order By: Relevance
“…In order to treat congenital or post-traumatic facial disfigurements in members of a particular racial or ethnic group successfully, surgeons require access to craniofacial databases based on accurate anthropometric measurements [3]. Previous studies have discovered facial features for distinguishing various races and ethnic groups using anthropometric methods [3][4][5]. These findings were introduced into clinical practice to quantify changes in the craniofacial framework [3].…”
Section: Introductionmentioning
confidence: 99%
“…In order to treat congenital or post-traumatic facial disfigurements in members of a particular racial or ethnic group successfully, surgeons require access to craniofacial databases based on accurate anthropometric measurements [3]. Previous studies have discovered facial features for distinguishing various races and ethnic groups using anthropometric methods [3][4][5]. These findings were introduced into clinical practice to quantify changes in the craniofacial framework [3].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have found a relationship between stature †Contributed equally to this work *Corresponding author (email: zhenglianbin@sina.com) and several different body parts such as the hands and feet (Abdel-Malek et al, 1990;Agnihotri et al, 2007;Agnihotri et al, 2008;Atamturk and Duyar, 2008;Cervantes et al, 1988;Fessler et al, 2005;Gordon and Buikstra, 1992;Habib and Kamal, 2010;Kanchan et al, 2008;Krishan, 2008a;Krishan, 2008b;Ozden et al, 2005;Rastogi et al, 2008;Reel et al, 2012;Sanli et al, 2005;Saxena, 1984;Sen and Ghosh, 2008;Zeybek et al, 2008), face and head (Baume and Buschang, 1983;Hautvast, 1971;Sahni et al, 2010), vertebral column (Jason and Taylor, 1995;Karakas et al, 2011;Nagesh and Pradeep Kumar, 2006;Pelin et al, 2005;Pininski and Brits, 2014;Qing et al, 2013;Terazawa et al, 1990;Tibbetts, 1981;Torimitsu et al, 2014;Zhang et al, 2008;Zhang et al, 2015), and upper-limb and lower-limb bones Aldegheri and Dall'Oca, 2001;Choi et al, 1997;Ikeda et al, 1977;Lavelle, 1977;…”
Section: Introductionmentioning
confidence: 99%
“…Osteometry seems to be the more favored and effective method in determining sex and race to an extent. 23 In this study, on plotting individual measurements of combined data against height, we found a highest correlation. In this modern era, the increased use of the regression formulae has definitely enhanced the precision of stature estimation.…”
Section: Discussionmentioning
confidence: 48%